2016
DOI: 10.1209/0295-5075/115/47003
|View full text |Cite
|
Sign up to set email alerts
|

From non-ergodic eigenvectors to local resolvent statistics and back: A random matrix perspective

Abstract: -We study the statistics of the local resolvent and non-ergodic properties of eigenvectors for a generalised Rosenzweig-Porter N × N random matrix model, undergoing two transitions separated by a delocalised non-ergodic phase. Interpreting the model as the combination of onsite random energies {ai} and a structurally disordered hopping, we found that each eigenstate is delocalised over N 2−γ sites close in energy |aj − ai| ≤ N 1−γ in agreement with Kravtsov et al. (New. J. Phys., 17 (2015) 122002) . Our othe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
131
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(152 citation statements)
references
References 37 publications
(80 reference statements)
10
131
0
Order By: Relevance
“…Note that m 0 minimizing Λ(m) is 1/2 in the entire region of nonergodic extended states 1 < γ < 2 in the limit ln N → ∞. This implies that the exponent in the power-law dependence (34) is 3/2 for all values of γ > 1, in agreement with general expectations and the results of works 12,13 . We conclude that the exact result of the RSB theory in this case is associated with the value of the exponent m 0 = 1/2 in the entire region of non-ergodic states.…”
Section: Application To Rosenzweig-porter Modelsupporting
confidence: 85%
See 1 more Smart Citation
“…Note that m 0 minimizing Λ(m) is 1/2 in the entire region of nonergodic extended states 1 < γ < 2 in the limit ln N → ∞. This implies that the exponent in the power-law dependence (34) is 3/2 for all values of γ > 1, in agreement with general expectations and the results of works 12,13 . We conclude that the exact result of the RSB theory in this case is associated with the value of the exponent m 0 = 1/2 in the entire region of non-ergodic states.…”
Section: Application To Rosenzweig-porter Modelsupporting
confidence: 85%
“…It was also suggested that the transition (referred to below as ergodic transition) from the extended ergodic (EE) to the non-ergodic extended (NEE) phases is a true transition as evidenced by the jump in the fractal dimensions rather than a crossover 11 . Existence of NEE phase and the transition from NEE to EE states has been recently proven 12,13 for an apparently different model, the random matrix theory with the special diagonal, suggested in 1960 by Rosenzweig and Porter (RP) 14 and generalized in Ref. 12 .…”
mentioning
confidence: 99%
“…30) has a well-defined scaling in N for each model as a function of its parameters. So this dynamical point of view is somewhat different from the closely recent studies based of the Green function G(z) as a function of the complex variable z = E + iη, where the imaginary part η introduced as a formal regularization can be chosen with various scalings with respect to the system size N in order to probe various regimes [26,32,50,72].…”
Section: Dynamics Within the Wigner-weisskopf Approximationmentioning
confidence: 95%
“…As recalled in the Introduction, the Generalized-Rosenzweig-Porter model is the simplest matrix model exhibiting a delocalized non-ergodic phase with an explicit multifractal spectrum for eigenvectors in [49], and has been analyzed recently from various points of view [32,50,51]. In this section, our goal is to show how the present dynamical approach is able to recover the multifractal spectrum obtained in [49].…”
Section: Generalized-rosenzweig-porter Matrix Modelmentioning
confidence: 97%
“…Recent results [21,48] suggest that a non-ergodic delocalized phase could still arise at large K (see however [49]). It will thus be very interesting to investigate this regime K 2 with our approach.…”
mentioning
confidence: 99%